Bullying Reporting Concerns as a Mediator Between School Climate and Bullying Victimization/Aggression. Issue 21 (November 2021) - Zhang, Saijun; Mulhall, Peter F.; Flowers, Nancy; Lee, Na Youn
This study aimed to examine whether bullying reporting concerns mediate the relationship between school climate and student bullying victimization as well as aggressive behavior. Data were from a sample of 301 students in Grades 6 to 8 in two minority-predominant schools in a large U.S. metropolitan area. Findings from bootstrapped structural equation modeling (SEM) analyses indicated that for male students, a higher level of perceived anti-bullying school climate was negatively associated with bullying reporting concerns, while the reporting concerns subsequently were positively associated with bullying victimization and aggressive behavior. For female students, perceived school climate was not associated with bullying reporting concerns, but the latter were also positively associated with bullying victimization and aggressive behavior. Therefore, bullying reporting concerns mediated the association between perceived school climate and bullying victimization as well as aggressive behavior for male but not female students. The findings suggest the importance of strengthening anti-bullying school climate to help students overcome bullying reporting concerns to achieve effective outcomes. The gender difference of associations between school climate and bullying reporting concerns may reflect the variation of bullying types experienced by male and female students, which calls for attention to the development of anti-bullying strategies that take into account gender differences and address various types of bullying.